Identification of a Human Immunodeficiency Virus Type 1 and Neurosyphilis Cluster in Vermont. (8th December 2020) - Singh, Devika; Switzer, William M; Belcher, Roy; Daltry, Daniel; Read, Jennifer S
Abstract: Background: Rates of syphilis in the United States have more than doubled over the last several decades, largely among men who have sex with men (MSM). Our study characterizes a cluster of neurosyphilis cases among people with human immunodeficiency virus 1 (HIV-1) in Vermont in 2017–2018. Methods: Vermont Department of Health disease intervention specialists conduct interviews with newly diagnosed HIV-1 cases and pursue sexual networking analyses. Phylogenetic and network analyses of available Vermont HIV-1 polymerase ( pol ) sequences identified clusters of infection. Fishers-exact and independent t -tests were used to compare people with HIV-1 within or outside an identified cluster. Results: Between 1 January 2017 and 31 December 2018, 38 residents were diagnosed with HIV-1 infection. The mean age was 35.5 years, 79% were male and 82% were White. Risk factors for HIV-1 included MSM status (79%) and methamphetamine use (21%). Eighteen cases (49%) had HIV-1 viral loads (VLs) >100 000 copies/mL and 47% had CD4 cell counts <200/mm 3 . Eleven of the 38 (29%) had positive syphilis serology, including four (36%) with neurosyphilis. Sexual networking analysis revealed a ten-person cluster with higher VLs at diagnosis (90% with VLs > 100 000 copies/mL vs 33%, P = 0.015). Phylogenetic analysis of pol sequences showed a cluster of 14 cases with sequences that shared 98%–100% HIV-1 nucleotide identity. Conclusions: This investigation of newly infected HIV-1 cases in Vermont led to identification of a cluster that appeared more likely to have advanced HIV-1 disease and neurosyphilis, supported by phylogenetic and network analyses. Abstract : Public health officials and clinicians in Vermont discovered a cluster of neurosyphilis cases among newly diagnosed individuals living with human immunodeficiency virus type 1 in 2017–2018, largely among men who have sex with men. This prompted a coordinated investigation to better characterize sexual networks and phylogenetics.